The long-term straw return resulted in significant differences in soil microbial community composition and community assembly processes between wheat and rice - Cui, Siyuan; Xu, Shangqi; Cao, Guangqiao; Zhu, Xinkai (Frontiers in Microbiology, 2025)
IntroductionStraw return is widely promoted as an environmentally sustainable practice to enhance soil health and agricultural productivity. However, the impact of varying straw return durations on soil microbial community composition and development remains insufficiently understood within a rice-wheat cropping system.MethodsIn this study, soil samples were collected during the wheat and rice harvesting periods following seven straw return durations: no straw return (NR) or 1, 3, 5, 7, 9, 11 years of straw return (SR1, 3, 5, 7, 9, 11), and microbial sequencing was performed.ResultsThe results revealed a biphasic pattern in alpha diversity (Chao1 and Shannon) of soil microbial communities with increasing straw return duration, characterized by an initial increase followed by a subsequent decrease. Specifically, SR9 in the rice group exhibited the highest Chao1 and Shannon values, while SR3 in the wheat group showed the highest values. PCoA indicated significant shifts in microbial communities due to straw return, particularly in the wheat group compared to NR. Straw return obvious changed six bacterial phyla (Verrucomicrobiota, Proteobacteria, Desulfobacterota, MBNT15, Actinobacteriota, and Gemmatimonadota) during the rice and wheat harvesting periods, especially Proteobacteria. Correlation analysis between environmental factors and bacterial communities demonstrated a significant impact on these factors, particularly pH and total organic carbon (TOC) (p < 0.05), on the soil bacterial community during rice harvest, indicating the microbial enrichment after straw return may be related to the accumulation of TOC. Furthermore, the bacterial community network in the rice harvesting period was found to be more complex, with lower network stability compared to the wheat harvesting period. This complexity is closely associated with TOC accumulation in rice fields. Deterministic processes, including homogeneous and heterogeneous selection, were found to play a crucial role in shaping the soil bacterial communities in both rice and wheat systems. Environmental factors significantly influenced microbial community assembly during straw return and recycling.DiscussionOur study enhances understanding of the impact of straw return on the diversity and assembly of soil microbial communities in the rice-wheat cropping system, which provide valuable insights for studying the mechanisms by which managing microbial communities after straw return can promote soil fertility restoration.